Work Motivation and Work Enthusiams of Madrasah Muallimin Muhammadiyah Yogyakarta Teachers - Mutakin, Deden (Universitas Muhammadiyah Surakarta, 2024)
Teachers at Madrasah Muallimin Muhammadiyah Yogyakarta have complex and diverse core tasks and functions that affect motivation and work spirit. The purpose of this research is to know the motivation of work and the work spirit of teachers at Madrasah Muallimin Muhammadiyah Yogyakarta. The study uses qualitative design through in-depth interviews and direct observation of 4 (four) teachers with non-permanent teacher status. Testing the credibility of data with member checking is by confirming the informant that the informants agree with the data found. The data analysis process is carried out through the stages of data collection, data reduction, data presentation, and data verification. The results of the research show that the spirit of work arises from the desire to accomplish this, which is reinforced by the presence of reasonable compensation. The need for affiliation becomes an important thing for teachers to become comfortable and enthusiastic at work. Maintaining harmony between teachers and having friends will have an impact on comfort and increased productivity at work. Great power brings great responsibility, and as a teacher grows competent, it will automatically affect greater responsibility.